Knowledge, Attitude and Practices Regarding Consumption of Carbonated Soft Drinks Among the Dental Students: A Cross-Sectional Study - Kiran Kumar Metta; Mawadah Ahmed Bin Afif; Nouf Mohammed Awwad AlThagfi; Rawan Osama Mohammed Ezzaddin; Bayader Emad Mansour Alam; Vinod Bandela (Association of Support to Oral Health Research (APESB), 2022)
Objective: To assess and evaluate the knowledge, attitude, and practices regarding the consumption of carbonated drinks among dental students. Carbonated drinks are pervaded by carbon dioxide and have more adverse effects since they are acidic in nature. Nowadays, these are consumed more widely globally, causing many systemic diseases; diabetes and obesity are common. Material and Methods: This study includes 204 individuals belonging to the age group of 18-26 years. A self-structured objective type cross-sectional questionnaire survey was conducted to assess the knowledge, attitude, and practice of dental students regarding carbonated drinks. The participants were instructed to mark the most appropriate correct answer from the given list of close-ended type questions. Results: Of 204 dental students, the study population includes 125 female and 79 male students. 98.5% of the students knew about carbonated drinks, while 1.5% were unaware. Conclusion:  Most participants preferred to have carbonated drinks even with their awareness about the ill effects of these drinks. Possible implications by the government authorities may probably increase awareness among the population.